Putting health in the hands of the people - Philippines. Department of Health. Integrated Community Health Services Project ([Manila] [DOH], 2003)
Contents: Module 1: an introduction to community health development -- module 2: helping communities to organize/mobilize -- module 3: community diagnosis, and participative planning -- module 4: Designing a barangay project to initiate community health development -- module 5: community-based health promotion -- module 5: annex 1 - sample KAB questionnaires and flow charts -- module 5: annex 2 - children's stories -- module 6: helping communities address health concerns through direct representation and collaborative partnerships -- module 7: helping communities participate in decision-making through lobbying and advocacy
Keywords: Community Health Services; Community Participation